Dose, parcelamento e modo de aplicação de nitrogênio em atributos nutricionais, agronômicos e tecnológicos de cultivares de sorgo sacarino - Ramos, Sérgio Bispo [UNESP] (2014)
Three experiments were conducted in field conditions with the objective of evaluating, in four cultivars of sweet sorghum, the effects of rates, times and manners of application of nitrogen in the stalk and ethanol yield, technological quality and N nutritional efficiency in the culture. It were installed two experiments with the same design, in a factorial 5x4 (five N rates and four cultivars), with three replicates in two distinct sites and another, in factorial scheme 4x4x2+4 (four cultivars, four strategies, two N application mode and four control), also with three replicates. The N application mode increased juice POL, purity, ATR and, the split with 20 kg ha-1 N, plus 70 kg ha-1 N at stages V4-V5 and 30 kg ha-1 N 10 days after, increased the ATR. The cultivars CVW 82158 and CVW 82028 obtained the greatest ATR values, with 76.45 and 59.82 kg t-1 respectively. The split of N applied at the groove produced 1327,8 and 1252,1 L ha-1 of ethanol for the cultivars CVW 82158 and CVW 82028 respectively. There was a significant relationship among accumulated N in the stalk dry matter mass with stalk and ethanol yield and between stalk with the nutritional efficiency of translocation, agronomic and physiologic of N